5 - Skills or Credentials? Comparing the Perspectives of Degree- and Non-degree-holding Ghanaian Graduates on the Value of Higher Education - Anyidoho, Nana Akua (Journal of Higher Education in Africa, 2022)
The massification of higher education, fuelled in part by demand from young people and their families, has coincided with more competition in the graduate labour market. This article seeks insight into the interpretative framework through which graduates view the relationship between higher education and the labour market. Specifically, given evidence of diminishing employment opportunities for graduates, the study examines the relative strengths of human capital theory and credentialism in explaining the value that young people continue to place on higher education. Using survey data from a sample of 2,036 Ghanaian higher education graduates, the article investigates the relative value students accord to skills and credentials through analysis of two self-report measures: satisfaction with their higher education experience, and, second, labour market expectations in respect of employment and income. Overall, non-degree holders self-assessed as having more skills training. Nonetheless, degree-holders generally were more satisfied with their educational achievements and had higher labour market expectations than those without degrees. These findings imply that young people value higher education less in terms of the skills they acquire and more in regards to the face-value of the qualifications they obtain, indicating a credentialist perspective that is in marked contrast to the human capital approach which undergirds policymaking on higher education in Ghana and much of the African continent.